On extraction of ground state deformation parameters from quasielastic and fusion excitation functions - Chandra Kumar; S. Nath (Physics Letters B)
Measurement of back-angle quasielastic scattering around the barrier, in conjunction with coupled-channels calculation, has been reported in recent years to be an effective and sensitive method to determine ground state deformation parameters of nuclei in the sd-shell as well as rare earth regions. Consequently, quasielastic scattering has been proposed to be a promising probe for extraction of ground state deformation parameters of short-lived radioactive nuclei. Theoretical investigations of quasielastic scattering and fusion for the system 28Si+144Sm, within the coupled-channels framework, are reported here. Fusion barrier height distribution is derived from measured fusion excitation function by an analytic method assuming the former to be a multi-Gaussian function. Bayesian analyses are carried out, both for fusion and quasielastic scattering data, to optimally determine quadrupole and hexadecapole deformation parameters of 28Si. The results suggest that extracted values are not free from ambiguities, thus necessitating utmost caution while extracting ground state deformation parameters following this method.